Nitrogen Photoelectrochemical Reduction on TiB2 Surface Plasmon Coupling Allows Us to Reach Enhanced Efficiency of Ammonia Production - Zabelina, Anna; Miliutina, Elena; Dedek, Jakub; Trelin, Andrii; Zabelin, Denis; Valiev, Rashid; Ramazanov, Ruslan; Burtsev, Vasilii; Popelkova, Daniela; Stastny, Martin; Svorcik, Vaclav; Lyutakov, Oleksiy (ACS catalysis, 2023)
Ammonia is one of the most widely produced chemicals worldwide, which is consumed in the fertilizer industry and is also considered an interesting alternative in energy storage. However, common ammonia production is energy-demanding and leads to high CO2 emissions. Thus, the development of alternative ammonia production methods based on available raw materials (air, for example) and renewable energy sources is highly demanding. In this work, we demonstrated the utilization of TiB2 nanostructures sandwiched between coupled plasmonic nanostructures (gold nanoparticles and gold grating) for photoelectrochemical (PEC) nitrogen reduction and selective ammonia production. The utilization of the coupled plasmon structure allows us to reach efficient sunlight capture with a subdiffraction concentration of light energy in the space, where the catalytically active TiB2 flakes were placed. As a result, PEC experiments performed at -0.2 V (vs. RHE) and simulated sunlight illumination give the 535.2 and 491.3 μg h-1 mgcat-1 ammonia yields, respectively, with the utilization of pure nitrogen and air as a nitrogen source. In addition, a number of control experiments confirm the key role of plasmon coupling in increasing the ammonia yield, the selectivity of ammonia production, and the durability of the proposed system. Finally, we have performed a series of numerical and quantum mechanical calculations to evaluate the plasmonic contribution to the activation of nitrogen on the TiB2 surface, indicating an increase in the catalytic activity under the plasmon-generated electric field.